Handbook on the changing geographies of the state: new spaces of geopolitics - Moisio, Sami; Koch, Natalie; Jonas, Andrew E. G.; Lizotte, Christopher; Luukkonen, Juho (Edward Elgar Publishing, 2020)
"This authoritative Handbook presents a comprehensive analysis of the spatial transformation of the state; a pivotal process of globalization. It explores the state as an ongoing project that is always changing, illuminating the new spaces of geopolitics that arise from these political, social, cultural, and environmental negotiations. Drawing together a diverse set of expert contributors, this book showcases compelling scholarship on the changing geographies of the state. Chapters examine the state from a range of theoretical angles and analyse a variety of relevant themes, including feminist geographies, the relationship between state and environment, urbanization, security geographies, nation-building, and geographical political economies. The book considers the state as spatial in both form and outlook, illustrating how it occupies existing and constantly-changing political geographic conditions, and how it is maintained by the practices of categorizing and managing territory. Taking a multidisciplinary approach, this Handbook will be a valuable resource for academics and students across a range of subjects, including human geography, international relations, political science, spatial planning, and urban studies. The key case studies explored will also provide valuable examples for scholars and policy-makers seeking a better understanding of the broad scope of geopolitics in a globalizing world"--